How Processing of Sensory Information From the Internal and External Worlds Shape the Perception and Engagement With the World in the Aftermath of Trauma: Implications for PTSD - Harricharan, Sherain; McKinnon, Margaret C.; Lanius, Ruth A. (Frontiers in Neuroscience, 2021)
Post-traumatic stress disorder (PTSD) is triggered by an individual experiencing or witnessing a traumatic event, often precipitating persistent flashbacks and severe anxiety that are associated with a fearful and hypervigilant presentation. Approximately 14-30% of traumatized individuals present with the dissociative subtype of PTSD, which is often associated with repeated or childhood trauma. This presentation includes symptoms of depersonalization and derealization, where individuals may feel as if the world or self is “dream-like” and not real and/or describe “out-of-body” experiences. Here, we review putative neural alterations that may underlie how sensations are experienced among traumatized individuals with PTSD and its dissociative subtype, including those from the outside world (e.g., touch, auditory, visual sensations) and the internal world of the body (e.g., visceral sensations, physical sensations associated with feeling states). We postulate that alterations in the neural pathways important for the processing of sensations originating in the outer and inner worlds may have cascading effects on the performance of higher-order cognitive functions, including emotion regulation, social cognition, and goal-oriented action, thereby shaping the perception of and engagement with the world. Finally, we introduce a theoretical neurobiological framework to account for altered sensory processing among traumatized individuals with and without the dissociative subtype of PTSD.